Ligature journal. (St Peters, NSW : Tiliqua Press Pty Ltd, 2015)
Ligature Journal is produced by design students; it investigates design, the thinking and ideas of design today. Our investigations into what design is today will take us into; what design can do for good or ill, the potential / possibilities of design, the ethics of design, the responsibilities of design, the philosophy of design, the impact of design (good or bad).
Title from spine.
Keywords: Design -- Australia -- Periodicals; Australian